Understanding cisplatin resistance using cellular models. - STORDAL, BRITTA KRISTINA (John Wiley, 2007)
Many mechanisms of cisplatin resistance have been proposed from studies of cellular models of resistance including changes in cellular drug accumulation, detoxification of the drug, inhibition of apoptosis and repair of the DNA adducts. A series of resistant models were developed from CCRF-CEM leukaemia cells with increasing doses of cisplatin from 100 ng/ml. This produced increasing resistance up to 7-fold with a treatment dose of 1.6 ?g/ml. Cisplatin resistance in these cells correlated with increases in the antioxidant glutathione, yet treatment with buthionine sulphoximine, an inhibitor of glutathione synthesis, had no effect on resistance, suggesting that the increase in glutathione was not directly involved in cisplatin resistance. Two models were developed from H69 SCLC cells, H69-CP and H69CIS200 using 100 ng/ml or 200 ng/ml cisplatin respectively. Both cell models were 2-4 fold resistant to cisplatin, and have decreased expression of p21 which may increase the cell?s ability to progress through the cell cycle in the presence of DNA damage. Both the H69-CP and H69CIS200 cells showed no decrease in cellular cisplatin accumulation. However, the H69-CP cells have increased levels of cellular glutathione and are cross resistant to radiation whereas the H69CIS200 cells have neither of these changes. This suggests that increases in glutathione may contribute to cross-resistance to other drugs and radiation, but not directly to cisplatin resistance. There are multiple resistance mechanisms induced by cisplatin treatment, even in the same cell type. How then should cisplatin-resistant cancers be treated? Cisplatin resistant cell lines are often more sensitive to another chemotherapeutic drug paclitaxel(H69CIS200), or are able to be sensitised to cisplatin with paclitaxel pre-treatment (H69-CP). The understanding of this sensitisation by paclitaxel using cell models of cisplatin resistance will lead to improvements in the clinical treatment of cisplatin resistant tumours.
PUBLISHED
Keywords: Cisplatin; Drug Resistance; Platinum; Chemotherapy; Glutathione; Paclitaxel; SCLC; Leukaemia